Ethnopolitics: regulatory principles of ethno-separatism - Bayramov, Imdad (Cuestiones Políticas, 2020)
The existing relationship, both in theory and in  concrete historical reality,  between economics, political development and ethnicity is substantial, to the point that ethno-politics can then be talked about as a novel field of study that, although based on political science, quickly transcends the order of the multi and interdisciplinary. It is order of ideas; this research article was aimed at identifying from the perspective of ethno-political analysis the principles that regulate the discourse of ethno-separatism. At the methodological level, documentary research technique was used. It is concluded that ethnicity goes through certain stages in its historical development. Political records show.  the existence of a multidimensional ethos that is observed culturally, socially, and democratically as a material and symbolic force that identifies some communities while differentiating them from others. Ethno-politics is in fact part of the concept of a political nation that preserves ethno-social-sofactors. From that moment on, the category of   ethno begins to subsumme the historical memory of the community and the national thought that determines its level of modern consciousness.